HARMONISATION OF REGULATIONS ON CROSS-BORDER RECEIVABLES IN INDONESIA IN AN EFFORT TO ACHIEVE LEGAL CERTAINTY AND PROTECTION FOR BUSINESS ACTORS - Arthur Daley; Januar Agung Saputera (INJOSEDU: International Journal of Social and Education, 2025)
This research examines the urgency of harmonizing cross-border factoring regulations in Indonesia in response to the dynamics of economic globalization and the need for legal certainty for business actors. Factoring has emerged as a strategic financing instrument, playing a significant role in maintaining cash flow stability, fostering MSME growth, and providing alternative funding sources, including through cross-border schemes. However, Indonesia has yet to establish a comprehensive legal framework governing such practices, resulting in legal uncertainty and potential disputes. Employing a normative juridical method with a statutory and comparative law approach, this research contrasts domestic regulations with legal practices in Singapore, Malaysia, and the Philippines. These countries have adopted adaptive legal models, including the implementation of the UNIDROIT Model Law on Factoring. In Indonesia, factoring practices are still based on the principle of freedom of contract under Article 1338 of the Civil Code, which, while offering flexibility, fails to provide standardized legal norms, thereby contributing to uncertainty and weakening competitiveness. The absence of specific regulations places Indonesia at a disadvantage in creating a conducive legal climate for international business actors. This study recommends the formulation of national regulations aligned with international legal principles to promote an inclusive, transparent, and globally competitive financing system. Harmonizing regulations is expected to enhance investor confidence and provide legal protection for all parties involved in cross-border factoring transactions.